PERANCANGAN SISTEM INFORMASI DOKUMENTASI BORANG AKREDITASI PROGRAM STUDI - Ahmaddul Hadi; Khairi Budayawan; Syukhri Syukhri (Universitas Negeri Padang, 2017)
One of quality assessment and the feasibility of higher education institutions and courses is accreditation. To achieve the desired accreditation value, universities and study programs must adjust the internal conditions in accordance with the standards given by the National Accreditation Board of Higher Education (BAN-PT). In most courses, all the data are scattered on different physical information systems and documents so that it takes more time and effort to integrate it into judgment. So required a system that is able to automatically retrieve and display the evaluation results with more efficient time and effort. One form of visualization that can meet it is by using a dashboard system that can integrate the entire contents of the supporting data so that when the evaluation process will get information about what parts are lacking or that already meet the standards. Keywords: Information System, Accreditation Form